Kebijakan Legislasi Pembaruan Pemidanaan Kitab Undang-Undang Hukum Pidana - Faisal Faisal; Anri Darmawan; Muh. Rustamaji; M. Witsa Firdaus; Rahmaddi Rahmaddi (University of Udayana, 2022)
The Dutch Colonial Criminal Code was born in the classical era. So that the concept of punishment is oriented towards acts with the argument of retaliation. So that criminal law enforcement is not in line with the development of national insight and global insight. The purpose of this research is to find out the renewal of the basic ideas of sentencing legislation policies, and the formulation of sentencing guidelines in the recently passed Criminal Code. The research method uses normative research. The results of the study show that legislation policy has a vision of building a national criminal law with the main mission of decolonization through systemic open codification. The basic idea of ??punishment reflects national goals and the value of balance. The purpose of sentencing is a rational choice that is formulated as a means of prevention, protection, protection and guidance. The Punishment Guidelines serve as a guide for judges to convict, pardon judges by not convicting, and impose sentences even though there are reasons for abolishing crimes Kitab Undang-Undang Hukum Pidana Kolonial Belanda lahir dalam era klasik. Sehingga konsep pemidanaan berorientasi pada perbuatan dengan dalil pembalasan. Sehingga penegakan hukum pidana tidak sejalan dengan perkembangan wawasan nasional dan wasasan global. Tujuan penelitian untuk mengetahui pembaruan ide dasar dari kebijakan legislasi pemidanaan, dan formulasi pedoman pemidanaan dalam Kitab Undang-Undang Hukum Pidana yang baru disahkan. Metode penelitian menggunakan penelitian normatif. Hasil kajian menunjukkan bahwa kebijakan legislasi memiliki visi membangun hukum pidana nasional dengan misi utama dekolonialisasi melalui kodifikasi terbuka bersifat sistemik. Ide dasar pemidanaan merefleksikan tujuan nasional dan nilai keseimbangan. Tujuan pemidanaan merupakan pilihan rasional yang diformulasikan sebagai sarana pencegahan, perlindungan, pengayoman, dan pembinaan. Pedoman Pemidanaan menjadi panduan hakim memidana, pemaafan hakim dengan tidak memidana, dan menjatuhkan pidana meskipun ada alasan penghapus pidana.